Monetary Policy Analysis in Indonesia: The Dynamic Relationship Between the BI Rate, Inflation, and the Rupiah Exchange Rate - Akhsan, Izzat Muhammad; Maharani, A S; Baity, I N (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
Monetary policy is crucial for sustaining Indonesia's macroeconomic stability, especially through the benchmark interest rate (BI Rate), which serves as the primary tool of Bank Indonesia. This research revisits the transmission of monetary policy within a contemporary framework marked by post-pandemic recovery, global monetary tightening, and domestic policy shifts under the new administration in 2024. Utilizing monthly time series data from January 2010 to March 2025, this study applies the Vector Autoregression (VAR) and Vector Error Correction Model (VECM) methodologies to examine the dynamic relationships among inflation, the exchange rate (USD/IDR), and the BI Rate. The results affirm the presence of long-term relationships among the three variables, aligning with earlier research, while also revealing significant short-term dynamics that indicate an increased sensitivity of the exchange rate and inflation to interest rate changes during times of global uncertainty. By extending the analysis period to 2025 and considering the context of post-pandemic recovery and policy transitions, this study offers updated empirical insights into the changing effectiveness of Indonesia's monetary policy transmission mechanism. The findings provide important implications for policymakers in developing interest rate strategies aimed at achieving a balance between inflation control, exchange rate stability, and economic recovery.